Harmonizing Development: Exploring Music and Musical Instruments as National Instruments in Colombia and Peru - M. Rojas Samper; F. D. Cortez Salcedo (Ибероамериканские тетради)
In Colombia and Peru, national music and national musical instruments are essential elements of cultural heritage, yet their importance goes beyond culture. The promotion of national musical instruments also pursues the two countries’ social, economic and political development goals. Traditional music, shaped in Colombia and Peru by the customs of indigenous peoples, African rhythms and the legacy of the Spanish Empire, embodies the rich history and culture of the indigenous peoples, helps to preserve traditions and national identity. The study seeks to answer the following questions related to the development and implementation of national instruments in Colombia and Peru: what are the key features of the national instruments in these countries? How are they developed and implemented? What are the challenges and opportunities arising from using them? How do they contribute to achieving the two countries’ development goals? The popularization of national music and musical instruments fosters the feeling of belonging and social cohesion, promotes tourism and plays an important role in education. Music is also related to political processes, as it has become an element of electoral campaigns and a factor to be taken into account when elaborating a national policy on culture and tourism. At the same time, the promotion of music and national instruments poses a number of challenges, including insufficient state funding, lack of official structures to promote local traditions, social and political barriers. Still, music is of paramount importance for Colombia and Peru: musical instruments are not only part of the entertainment industry but also national symbols that harmonize development and cultivate cultural pride.